A teratological case in antenna of Nysson tridens Gerstäcker, 1867 (Hymenoptera: Crabronidae) - Can, İlyas and Ruchin, Alexander B. (Acta Biologica Sibirica, 2024)
A case of asymmetry and hypertrophy on the right antenna in the kleptoparasite wasp Nysson tridens Gerstaecker, 1867 is described from Russia. This is the first antennal teratology in the family Crabronidae (Hymenoptera).